2004
DOI: 10.1165/rcmb.2003-0136oc
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis and Necrosis Induced by Cyclic Mechanical Stretching in Alveolar Type II Cells

Abstract: Alveolar type II (ATII) cells are exposed to mechanical stretch during breathing and mechanical ventilation. Increased stretch may contribute to lung injury. The influence of three stretching patterns (characterized by frequency [min(-1)] - increase in surface area [%]: S40-13, S60-13, S40-30) on parameters of apoptosis, necrosis, and membrane integrity of rat ATII cells was compared with that in static cultures. The S40-13 stretching pattern simulated normal breathing. The other patterns were chosen to study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
85
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(92 citation statements)
references
References 33 publications
6
85
0
1
Order By: Relevance
“…Similar studies in ATII cells have Stretch-induced gene transfer and the cytoskeleton RC Geiger et al had similar findings, and have also shown that these levels of stretch do not induce necrosis. 16 Taken together, these results suggest that cell proliferation is not required for stretch-increased transfection efficiency.…”
Section: Cyclic Stretch Causes Increased Gene Expression Without Incrmentioning
confidence: 80%
“…Similar studies in ATII cells have Stretch-induced gene transfer and the cytoskeleton RC Geiger et al had similar findings, and have also shown that these levels of stretch do not induce necrosis. 16 Taken together, these results suggest that cell proliferation is not required for stretch-increased transfection efficiency.…”
Section: Cyclic Stretch Causes Increased Gene Expression Without Incrmentioning
confidence: 80%
“…The biological responses of epithelial cells to deformation are numerous: for example, cyclic deformation of rat primary alveolar epithelial cells increases the level of cell death compared with static deformation (56); cyclic stretch induces apoptosis and necrosis in alveolar type II cells (25); stretch increases paracellular permeability by disrupting tight-junction structure and function (6); and deformation induces inflammatory signaling (59). Mechanical events such as stress failure of the plasma membrane (11,58) underlie potential mechanisms of damage in ventilator-induced lung injury (57).…”
Section: Discussionmentioning
confidence: 99%
“…1,2 The primarily biological mechanisms include the release of inflammatory mediators and oxygen radicals, leading to end-organ epithelial cell apoptosis and organ dysfunction. [3][4][5] In a previous study, a high tidal volume in mouse lung could induce the activation of c-Jun N-terminal kinase (JNK), an increase in macrophage inflammatory protein-2 (MIP-2) expression, and the migration of neutrophil into the lung. 6 Activated JNK is dependent on the activation of apoptosis signal-related kinase 1 (ASK1), which is identified as a member of the mitogen-activated protein kinase (MAPK) family, in cultured bronchial epithelium.…”
Section: Introductionmentioning
confidence: 99%